The use of compression stockings produces lower Interleukin-6 (IL-6) levels, Higher American Orthopaedic Foot and Ankle Society Score (AOFAS), and does not produce higher alkaline phosphatase level in postoperative patients with fracture around the ankle - Gede Agung Krisna Yudha; I Ketut Siki Kawiyana; Ketut Gede Mulyadi Ridia; I Ketut Suyasa; I Gede Eka Wiratnaya (Intisari Sains Medis, 2021)
Background: Fractures around the ankles are common injuries. The use of compression stockings is one of the postoperative modalities that has been widely used in developing countries but is rarely used in Indonesia. This study aimed to determine the effect of using compression stockings on changes in inflammatory biomarkers level and functional outcomes in postoperative patients with fractures around the ankle.Methods: This study was a randomized clinical trial (post-operative-only design) in 26 patients with fractures around the ankle. The study subjects were divided into groups using postoperative compression stockings and groups without compression stockings. Its efficacy was assessed by measuring levels of Interleukin-6 (IL-6), Alkaline Phosphatase (ALP), and American Orthopedic Foot and Ankle Society (AOFAS) scores. Data were analyzed using SPSS version 20 for Windows.Results: Postoperative 24-hour IL-6 levels were not significantly different (p=0.200; -59.93–266.42), but they were significantly different postoperatively in 3 days (p = 0.001; 8.76-30.21), 14 days (p=0.015; 2.40-20.49), and 30 days (p=0.000; -15.49–[-5.03]). ALP was not different significantly, both at 24 hours (p=0.160; -16.0-2.80), 3 days (p=0.072; -0.65-14.19), 14 days (p=0.098; -1,310–12,54), and 30 days (p=0.419; -5.00–11.61) after surgery. The AOFAS scores was different significantly 30 days postoperatively (p=0.000; -3.915– [-1.469]).Conclusion: The use of compression stockings can be considered as postoperative therapy to lower the IL-6 levels but do not affect ALP levels in postoperative patients with fractures around the ankle. The use of compression stocking resulted in a higher AOFAS score than without wearing compression stockings in postoperative patients with fractures around the ankle.